Corporate Governance on Organizational Performance: A Study of Commercial Banks in Butwal Sub-Metropolitan City - Rijal, Deepa (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study intends to examine the effect of Corporate Governance on Organizational performance in Commercial Bank. Methods: The study employed a purposive sampling method to gather data from 240 employees of commercial banks in Butwal. A self-administered questionnaire incorporating a precise seven-point Likert scale was utilized. Additionally, the research adopted a descriptive and causal-comparative design, supported by an extensive range of statistical techniques, including Mean, Standard Deviation, Correlation, Independent t-test, one-way ANOVA, Mann-Whitney U test, Kruskal-Wallis H test, R-square, Hypothesis testing, and Regression, all carefully selected to ensure rigorous data analysis. Results: The resultss indicates that social awareness is the major factor for organizational performance of commercial banks in Butwal Sub-Metropolitan City. Banks that actively engage in socially responsible practices, such as community involvement, customer-centric policies gain customer trust, and improve employee morale. This, in turn, leads to increased customer loyalty and sustainable growth. The findings emphasize that corporate governance frameworks integrating social awareness contribute to long-term success in the banking sector. Conclusion: This research concludes that Social Awareness is the major determinants of Organizational performance. Thus, Banking organizations must focus on Social Awareness programs like financial literacy, Community Development Programs which build a sense of trust and goodwill with customers and enhanced its reputation as a responsible corporate citizen which leads to long term sustainable growth of banking organization.